A new teaching concept on quantum physics in secondary schools - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2020)
In this article, an approach to integrate contemporary quantum physics into secondary school teaching is presented. The Erlanger concept on quantum optics provides an experimental-based guideway to aspects of modern quantum physics. We avoid the traditional historical approach in order to overcome the lack of modern concepts of quantum physics. In an acceptance survey, initial empirical evidence for the acceptance of the developed explanatory approaches was evaluated.
Keywords: quantum optics; anticorrelation factor; single Photons; acceptance survey

A new teaching-learning sequence to promote secondary school students' learning of quantum physics using Dirac notation - Bitzenbauer, Philipp; Hennig, Fabian; Förster, Moritz; Tóth, Kristóf (Physics Education, 2024)
This paper describes the design of a new teaching-learning sequence on quantum physics aimed at upper secondary school students. In this teaching-learning sequence, GeoGebra simulations and interactive screen experiments are used to investigate the behaviour of a single photon at beam splitter and single photon interference in a Michelson interferometer. We propose a minimal formalism using Dirac notation, which avoids complex numbers and elaborate vector calculus, to make a quantitative description of the quantum optics experiments accessible to secondary school students. With this new educational pathway, we take into account findings from physics education research, which suggest that the introduction of a mathematical formalism tailored to students' abilities might help them to overcome naive-realist views of quanta or space-time descriptions of quantum phenomena, while at the same time facilitating a transition to a functional understanding of quantum model

Assessing Engineering Students’ Conceptual Understanding of Introductory Quantum Optics - Bitzenbauer, Philipp; Veith, Joaquin M.; Girnat, Boris; Meyn, Jan-Peter (Physics, 2022)
Quantum technologies have outgrown mere fundamental research in laboratories over recent years, and will facilitate more and more potentially disruptive applications in a wide range of fields in the future. In foresight, qualification opportunities need to be implemented in order to train qualified specialists, referred to as the future quantum workforce, in various fields. Universities world-wide have launched qualification programmes for engineers focusing on quantum optics and photonics. In many of these programmes, students attend courses on quantum physics contextualized via quantum optics experiments with heralded photons, because: (1) their experimental and physical foundations may be directly leveraged to teaching a number of quantum technology applications, and (2) physics education research has provided empirical evidence, according to which such quantum optics-based approaches are conducive to learning about quantum concepts. While many teachers are confident about the effectiveness of their concepts, there is little empirical evidence due to the lack of content-area-specific research tools. We present a 16-item concept inventory to assess students’ conceptual understanding of quantum optics concepts in the context of experiments with heralded photons adopted from a test instrument published in the literature. We have administered this Quantum Optics Concept Inventory as a post-test to N=216" role="presentation">N=216 students after instruction on quantum optics as part of an undergraduate engineering course. We evaluated the instruments’ psychometric quality, both in terms of classical test theory, and using a Rasch scaling approach. The Quantum Optics Concept Inventory enables a reliable measure (α=0.74" role="presentation">α=0.74), and the data gathered show a good fit to the Rasch model. The students’ scores suggest that fundamental quantum effects pose striking learning hurdles to the engineering students. In contrast, most of the students are able to cope with the experimental and technical foundations of quantum optics experiments with heralded photons and their underlying principles, such as the coincidence technique used for the preparation of single-photon states. These findings are in accordance with prior research, and hence, the Quantum Optics Concept Inventory may serve as a fruitful starting point for future empirical research with regard to the education of the future quantum workforce.
Keywords: quantum optics; concept inventory; Rasch scaling; quantum technology

Assessing Learners’ Conceptual Understanding of Introductory Group Theory Using the CI²GT: Development and Analysis of a Concept Inventory - Veith, Joaquin M.; Bitzenbauer, Philipp; Girnat, Boris (Education Sciences, 2022)
Prior research has shown how incorporating group theory into upper secondary school or undergraduate mathematics education may positively impact learners’ conceptual understanding of mathematics in general and algebraic concepts in particular. Despite a recently increasing number of empirical research into student learning of introductory group theory, the development of a concept inventory that allows for the valid assessment of a respective conceptual understanding constitutes a desideratum to date. In this article, we contribute to closing this gap: We present the development and evaluation of the Concept Inventory of Introductory Group Theory—the CI2GT. Its development is based on a modern mathematics education research perspective regarding students‘ conceptual mathematics understanding. For the evaluation of the CI2GT, we follow a contemporary conception of validity: We report on results from two consecutive studies to empirically justify that our concept inventory allows for a valid test score interpretation. On the one hand, we present N=9" role="presentation" style="max-height: none; display: inline; line-height: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; position: relative;">N=9 experts‘ opinions on various aspects of our concept inventory. On the other hand, we administered the CI2GT to N=143" role="presentation" style="max-height: none; display: inline; line-height: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; position: relative;">N=143 pre-service primary school teachers as a post-test after a two weeks course into introductory group theory. The data allow for a psychometric characterization of the instrument, both from classical and probabilistic test theory perspectives. It is shown that the CI2GT has good to excellent psychometric properties, and the data show a good fit to the Rasch model. This establishes a valuable new concept inventory for assessing students’ conceptual understanding of introductory group theory and, thus, may serve as a fruitful starting point for future research into student learning of abstract algebra.<br
Keywords: algebra; groups; magmas; secondary school; mathematics education

ChatGPT in physics education: A pilot study on easy-to-implement activities - Bitzenbauer, Philipp (Contemporary Educational Technology, 2023)
Large language models, such as ChatGPT, have great potential to enhance learning and support teachers, but they must be used with care to tackle limitations and biases. This paper presents two easy-to-implement examples of how ChatGPT can be used in physics classrooms to foster critical thinking skills at the secondary school level. A pilot study (n=53) examining the implementation of these examples found that the intervention had a positive impact on students’ perceptions of ChatGPT, with an increase in agreement with statements related to its benefits and incorporation into their daily lives.<br

Classical Mechanics Key Topics in Physics Teacher Education: Results of an Exploratory Mind Map Study - Bitzenbauer, Philipp; Winkler, Bianca; Veith, Joaquin M. (European Journal of Educational Research, 2023)
Although the central role of classical mechanics in physics teacher education is undisputed, divergent interests and perspectives from different disciplinary cultures might exist when thinking about how to best support pre-service teachers' professional development. In this article, we report the results of an exploratory mind map study to investigate which classical mechanics topics are regarded essential for physics teacher education according to N = 29 experts from different physics disciplines. The participants’ mind maps were analyzed using a category system and frequency analysis was applied. The results hint at similarities and differences in terms of key topics to be addressed in physics teacher education on classical mechanics according to experts from different physics disciplines, e.g., in terms of the depth of mathematics considered relevant for physics teacher education.<br

Cross-age study on secondary school students’ views of stars - Bitzenbauer, Philipp; Navarrete, Sarah; Hennig, Fabian; Ubben, Malte; Veith, Joaquin M. (Physical Review Physics Education Research, 2023)
Research in astronomy education has uncovered that many learners possess limited and fragmented understanding of stars. The corresponding misconceptions manifest in various areas such as star formation, size, the relationship between stars and planets, and their position in space and have been shown to persist across different age groups and educational settings, highlighting the need for further investigation. This paper presents the findings of an empirical study that examines secondary students’ views of stars and their evolution throughout their secondary school education. We designed and evaluated an instrument for assessing students’ views of stars in five domains (stars and the solar system, formation and evolution of stars, general properties and motion of stars, (sub-)stellar objects, as well as color and brightness). The instrument creation process involved several steps, including literature-based item development, an expert survey with faculty members, and a quantitative pilot study with a sample of N=390 secondary school and college students. This process led to a final version of the instrument that exhibits good psychometric properties. We used this new instrument in a cross-age study to investigate the alignment of secondary students’ ideas about stars with scientific views across different stages of secondary education. The sample of this main study comprised a total of N=366 learners, including 148 lower (aged 13–14 years), 151 middle (aged 15–16 years), and 67 upper (aged 17–18 years) secondary school students. Our study findings reveal a progressive development of students’ perspectives on star-related topics throughout their school education: Using analyses of variance and conducting pairwise post hoc comparisons, we observed a statistically significant increase in the proportion of responses aligning with scientific views across all aspects of stars examined in this study, as students progressed from lower secondary to upper secondary levels. We further report on widely held views of stars among our study participants that do not align with the scientific views and discuss the implications of our findings for both educational research and practic

Development of a Test Instrument to Investigate Secondary School Students’ Declarative Knowledge of Quantum Optics - Bitzenbauer, Philipp (European Journal of Science and Mathematics Education, 2021)
This article reports the development and validation of a test instrument to assess secondary school students’ declarative quantum optics knowledge. With that, we respond to modern developments from physics education research: Numerous researchers propose quantum optics-based introductory courses in quantum physics, focusing on experiments with heralded photons. Our test instrument’s development is based on test development standards from the literature, and we follow a contemporary conception of validity. We present results from three studies to test various assumptions that, taken together, justify a valid test score interpretation, and we provide a psychometric characterization of the instrument. The instrument is shown to enable a reliable (α = 0.78) and valid survey of declarative knowledge of quantum optics focusing on experiments with heralded photons with three empirically separable subscales.<br
Keywords: quantum physics; test development; validation

Dichte im Physikunterricht: Pilotierung einer deutschen Version des Density Survey - Zenger, Tim; Bitzenbauer, Philipp (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2021, 2022)

Effect of an introductory quantum physics course using experiments with heralded photons on preuniversity students’ conceptions about quantum physics - Bitzenbauer, Philipp (Physical Review Physics Education Research, 2021)
We conducted a quasiexperimental study in order to investigate the effect of a teaching concept on quantum physics based on coincidence and correlation experiments with heralded photons on preuniversity students’ conceptions of quantum physics (experimental group, N=150). We compare the results with the traditional curriculum’s effect (control group, N=130) at German secondary schools using a questionnaire to assess students’ conceptions of quantum physics adapted from the literature. The results show that students introduced to quantum physics using the quantum optics concept acquire conceptions of quantum physics that are significantly less influenced by classical mechanistic and deterministic conceptions than those of the control group. In more detail, correlation and principal component analysis results indicate that the conceptions acquired by experimental group students are more consistent than those of the control group students.<br
Keywords: preuniversity students' conceptions; quantum physics; introductory quantum physics course

Empirische Forschung im Erlanger SchülerForschungsZentrum ESFZ - Erste Ergebnisse einer explorativen Fragebogenstudie - Fösel, Angela; Bitzenbauer, Philipp (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung - virtuell 2021, 2021)
Seit etwas mehr als 10 Jahren gibt es das Erlanger SchülerForschungsZentrum ESFZ (https://esfz.nat.uni-erlangen.de/), verortet am Department Physik der Friedrich-Alexander-Universität (FAU) Erlangen-Nürnberg. Schülerinnen und Schüler, die Lust und Spaß am Forschen und Tüfteln an eigenen Projektideen aus dem Bereich Naturwissenschaft und Technik haben, finden hier Unterstützung in einem wissenschaftlich-professionellen Rahmen: In einwöchigen Forschungscamps nutzen bis zu 25 Jugendliche die zur Verfügung gestellte Infrastruktur, um über den Unterricht hinaus unter Betreuung von studentischen Tutor*innen und Wissenschaftler*innen an eigenen Projektideen aus Naturwissenschaft und Technik zu forschen. Im Rahmen einer explorativen Fragebogenstudie soll erhoben werden, wie Schülerinnen und Schüler, die bereits an ESFZ-Forschungscamps teilgenommen haben, die Betreuung in den Camps erlebt haben, wie sehr sie sich in das Forschungsleben eingebunden fühlten, und welche Fähigkeiten und Fertigkeiten ihrer Meinung nach in den Camps erlernt und gefördert wurden. Im Beitrag werden der für die Erhebung konzipierte Online-Fragebogen und auch die Modalitäten der Durchführung vorgestellt. Die Ergebnisse einer ersten Pilotstudie werden präsentiert, und es werden auch mögliche Forschungsfragen für daran anknüpfende Untersuchungen im Rahmen der empirischen Begleitforschung zum Erlanger SchülerForschungsZentrum diskutier
Keywords: Schülerforschungszentrum; empirische Forschung; außerschulische Lernorte

Entwicklung eines Konzepttests zur Astronomie: Erste Ergebnisse - Bitzenbauer, Philipp; Ubben, Malte (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2022)
Sterne und das Weltall sind bei Lernenden seit jeher hoch im Kurs, wie die Ergebnisse von Interessensstudien zeigen. Empirische Instrumente zur Erhebung von Vorstellungen oder Konzeptverständnissen Lernender zu Konzepten der Astronomie sind jedoch rar. Im vorgestellten Projekt wird die Entwicklung und Pilotierung von solchen Instrumenten für den deutschen Sprachraum angestrebt. Wir berichten in diesem Beitrag die Ergebnisse der Pilotierung eines ersten Konzepttests zu Sternen, der auf international bereits etablierten Concept Inventories basiert.<br

Erklärvideos zur Quantenverschränkung — Ein Unterrichtskonzept mit Erklärvideos und Hinweise zu ihrer Auswahl - Bitzenbauer, Philipp; Heusler, Stefan; Ubben, Malte (Naturwissenschaften im Unterricht. Physik, 2023)

Ermittlung von Anforderungen an künftige Quanten-Fachkräfte: Zwischenbericht aus der Delphi-Studie - Gerke, Franziska; Müller, Rainer; Bitzenbauer, Philipp; Ubben, Malte; Weber, Kim Alessandro (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung - virtuell 2021, 2021)
Mit den neuen Quantentechnologien, den QT 2.0, ergeben sich spezielle Anforderungen an die Fach-kräfte, die mit diesen arbeiten werden. Ziel der vorgestellten Delphi-Studie ist die Ermittlung von Kompetenzen für und Anforderungen an die künftigen Quanten-Fachkräfte. Damit bilden die Er-gebnisse dieser Delphi-Studie die Basis für die Entwicklung eines Competence Frameworks im eu-ropäischen Quantum Flagship Projekt QTEdu CSA. Darüber hinaus liefert die Delphi-Studie Ein-schätzungen zu Begriffs- bzw. Definitionsschärfung sowie Prognosen zur künftigen Relevanz der einzelnen Säulen der QT 2.0, also Quantencomputing, Quantensimulation, Quantensensorik/Metro-logie und Quantenkommunikation, sowie auch den Enabling Technologies. Vorgestellt werden in diesem Beitrag vorwiegend die aktuellen Zwischenergebnisse der ersten Hauptrunde, die auf denen einer Pilotrunde aufbauen, und die in einer abschließenden Befragungs-runde bewertet und ergänzt werden sollen.<br
Keywords: Quantum Awareness; Quantum Literacy; Competence Framework

Evaluation eines Unterrichtskonzepts zur Quantenoptik mit Einzelphotonenexperimenten – Ergebnisse einer Pilotstudie - Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen, 2020)

Exploring German Secondary School Students’ Conceptual Knowledge of Density - Zenger, Tim; Bitzenbauer, Philipp (Science Education International, 2022)
This article reports on the development and piloting of a German version of a concept test to assess students’ conceptual knowledge of density. The concept test was administered in paper-pencil format to 222 German secondary school students as a post-test after instruction in all relevant concepts of density. We provide a psychometric characterization of the instrument based on the student responses. Therefore, we use methods from classical test theory and item response theory. Our analysis shows that our concept test has good psychometric properties. Furthermore, it is shown to enable a reliable (α= 0.77) survey of students’ conceptual knowledge of density. Finally, we use the student responses to identify secondary school students’ difficulties with the density concept. We replicate student difficulties on density from the literature, but our study also reveals some new difficulties.<br
Keywords: concept inventory; student difficulties; density

Exploring Learning Difficulties in Abstract Algebra: The Case of Group Theory - Veith, Joaquin M.; Bitzenbauer, Philipp; Girnat, Boris (Education Sciences, 2022)
In an earlier contribution to Education Sciences we presented a new concept inventory to assess students’ conceptual understanding of introductory group theory—the CI2GT. This concept inventory is now leveraged in a pretest-post-test design with N = 143 pre-service teachers to enrich this body of work with quantitative results. On the one hand, our findings indicate three recurring learning difficulties which will be discussed in detail. On the other hand, we provide a summative evaluation of the Hildesheim Teaching Concept and discuss students’ learning gain in different sub-domains of group theory. Together, the results allow for an empirical perspective on educational aspects of group theory and thus bridge the gap between qualitative and quantitative research in this field which constitutes a desideratum to date. <br
Keywords: algebra; group theory; secondary school; mathematics education

Exploring the effect of a phenomenological teaching-learning sequence on lower secondary school students' views of light polarisation - Bitzenbauer, Philipp; Tóth, Kristóf; Michelini, Marisa (Physics Education, 2024)
The wave model of light in general, and the phenomenon of light polarisation in particular, are difficult topics for secondary school students. Prior research has indicated that a model-free phenomenological teaching approach may be fruitful in helping students overcome some of the widespread learning obstacles. These phenomenological approaches are characterised by their departure from abstract and mechanistic models of light, opting instead to prioritise students' observations throughout the exploration of phenomena and experiments, unburdened by mathematical formalism or theoretical models. In this paper, we present a three-lessons phenomenological teaching-learning sequence on light polarisation. We evaluated of the teaching concept in classroom practise and analysed ways of thinking about light polarisation among N = 110 students (aged 12–14 years) who participated in the intervention using qualitative content analysis of free-text responses. The results provide preliminary empirical evidence that the presented instructional approach can contribute to the development of a qualitative understanding of polarisation among learners in introductory optic

Exploring the effect of a phenomenological teaching-learning sequence on lower secondary school students’ views of light polarisation - Tóth, Kristóf; Michelini, Marisa; Bitzenbauer, Philipp (Physics Education, 2024)
The wave model of light in general, and the phenomenon of light polarisation in particular, are difficult topics for secondary school students. Prior research has indicated that a model-free phenomenological teaching approach may be fruitful in helping students overcome some of the widespread learning obstacles. These phenomenological approaches are characterised by their departure from abstract and mechanistic models of light, opting instead to prioritise students’ observations throughout the exploration of phenomena and experiments, unburdened by mathematical formalism or theoretical models. In this paper, we present a three-lessons phenomenological teaching-learning sequence on light polarisation. We evaluated of the teaching concept in classroom practise and analysed ways of thinking about light polarisation among N = 110 students (aged 12-14 years) who participated in the intervention using qualitative content analysis of free-text responses. The results provide preliminary empirical evidence that the presented instructional approach can contribute to the development of a qualitative understanding of polarisation among learners in introductory optics.
CRIS-Team Scopus Importer:2024-04-12
Keywords: light; optics; phenomena; polarisation

Exploring the relationship between students’ conceptual understanding and model thinking in quantum optics - Bitzenbauer, Philipp; Ubben, Malte (Frontiers in Quantum Science and Technology, 2023)
Learning quantum physics is essential for understanding the physical world. However, learning about quantum phenomena and principles poses a challenge as many of the phenomena that are observed at the quantum level cannot be directly observed or intuitively understood in terms of classical physics or thinking. Models play an important role in learning quantum physics by providing conceptual frameworks and visual representations that allow reasoning about and predicting the behavior of quantum systems. Therefore, understanding models is an essential part of learning quantum physics. In this article, we report the results of an exploratory survey study (N = 116) investigating the relationship between secondary school students’ conceptual understanding and model thinking in quantum optics with a particular focus on photons. The findings suggest a strong positive correlation between students’ functional understanding of the photon model and their conceptual understanding of quantum optics. This study contributes to our understanding of how students learn and make sense of quantum concepts through the use of models and may inform the development of instructional strategies for quantum physics education and outreach.<br

Exploring the Relationship Between Surface Features and Explaining Quality of YouTube Explanatory Videos - Bitzenbauer, Philipp; Höfler, Sebastian; Veith, Joaquin M.; Winkler, Bianca; Zenger, Tim; Kulgemeyer, Christoph (International Journal of Science and Mathematics Education, 2023)
Physics education research on explanatory videos has experienced a boost in recent years. Due to the vast number of explanatory videos available online, e.g. on YouTube, finding videos of high explaining quality is a challenging task for learners, teachers, and lecturers alike. Prior research on the explaining quality of explanatory videos on classical mechanics topics has uncovered that the surface features provided by YouTube (e.g. number of views or likes) do not seem to be suitable indicators of the videos’ explaining quality. Instead, the number of content-related comments was found to be statistically significantly correlated with the explaining quality. To date, these findings have only been observed in the context of explanatory videos on classical mechanics topics. The question arises whether similar correlations between the explaining quality and YouTube surface features can be found for videos on topics that are difficult to access visually and verbally, for example from quantum physics. Therefore, we conducted an exploratory study analyzing the explaining quality of N = 60 YouTube videos on quantum entanglement and tunnelling. To this end, we made use of a category-based measure of explanatory videos’ explaining quality from the literature. We report correlations between the videos’ explaining quality and the surface features provided by YouTube. On the one hand, our results substantiate earlier findings for mechanics topics. On other hand, partial correlations shed new light on the relationship between YouTube’s surface features and explaining quality of explanatory videos.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Entanglement; Explaining quality; Explanatory videos; Quantum physics; Surface features; Tunnelling

Flipped classroom in physics teacher education: (how) can students' expectations be met? - Bitzenbauer, Philipp; Hennig, Fabian (Frontiers in Education, 2023)
In this paper, we describe the development of a flipped classroom concept for physics teacher education along (a) design criteria from the literature, and (b) students' needs and expectations extracted from an exploratory pre-study (N = 21). We implemented it in a physics education course at Leipzig University, Germany, and report results of its empirical evaluation (N = 29). Our results hint at both, strengths and weaknesses of the developed flipped classroom concept, and hence, pave the way for further research into the use of flipped classroom scenarios in physics teacher education.<br

Förderung eines funktionalen Modellverständnisses Lernender in der Quantenphysik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2020, 2021)

Fostering experimental competences of prospective physics teachers - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2021)
Physics teachers are often faced with the challenge of having to set up difficult experiments, or they have to consciously manipulate parameters in order to be able to demonstrate a phenomenon convincingly. Comprehensive laboratory courses are standard procedure in any study program for prospective physics teachers. However, many students, even after completing standard laboratory courses, show difficulties in standard experimental situations, such as measuring an electric current. We report on a new seminar concept for students in physics teacher study programs. This concept is based on the current state of research in physics education, on the teachers' professional competences, and on the modelling of experimental competence, justifying its embedding in teacher training. We present first results of a pilot study carried out to evaluate the seminar.<br
Keywords: experimental competence; teacher education; professional knowledge; assessment

Fostering students' conceptions about the quantum world - results of an interview study - Bitzenbauer, Philipp; Meyn, Jan-Peter (Progress in Science Education, 2021)
Background: Quantum physics is both a highly topical and challenging topic of physics education. Learning quantum physics is inherently difficult because it is unimaginative, counterintuitive and fundamentally different from what learners know from their everyday life and classical physics. The results of recent studies underline that students are often not aware of the relevance of quantum physics and its technologies for their own lives, which makes studying quantum physics even more difficult. This is the starting point of this article: With the Erlanger teaching concept, we present an introductory teaching concept for quantum physics at secondary schools with the aim, among others, to raise students’ awareness of the importance of modern quantum technologies today and in the future. Purpose: In order to evaluate which conceptions about the quantum world arise among students who are introduced to quantum physics with the Erlanger concept, we conducted an interview study. Sample/Setting: A random sample of N = 25 students was interviewed after the intervention (15 male, 10 female) in order to answer the questions mentioned above. The interviews had a duration of 25 – 40 minutes. Prior to the intervention, none of the students had any classroom instruction in quantum physics. Design and Methods: The students’ answers were transcribed and then evaluated on the basis of deductive and inductive categories using qualitative content analysis. The coding was done by independent coders (κ=0.84,95% - CI [0.68;1.00]). Additionally, a cluster analysis was performed and a three-cluster solution was extracted. The three clusters could be interpreted in terms of content and thus facilitate the characterization of occurring types of students’ conceptions after the intervention. Results: After the intervention with our concept, we found elaborated conceptions about the quantum world with the majority of respondents. 11 of the 25 students (cluster 1, labelled Primarily elaborate conception) are aware of the striking differences between quantum and classical physics, as all students in this cluster characterize the quantum world via effects or aspects that do not exist in classical physics. The importance of quantum physics for future technologies was named by the students combined in the cluster 2, labelled Quantum world as the world of technology. 10 of the students interviewed (cluster 3, labelled Quantum world as a classical world on a small scale) seem to stick to their pre-conceptions dominated by classical ways of thinking. Conclusions: Our article provides implications for both classroom practice and future research. For classroom practice, the Erlanger teaching concept serves as a proposal to bridge the gap between quantum physics and the everyday life of the learners. In addition, the results of the interview study presented in this paper make a contribution to the empirical research on students’ conceptions about quantum physics. We not only find individual, independent conceptions of learners, but we also show that there are dependencies between them, allowing us to extract types of conceptions. The extraction of such types of student conceptions for various further concepts of quantum physics will be part of future research and could contribute to our understanding of learning processes in quantum physics. Keywords: quantum physics, interview study, cluster analysis, teaching concept</e
Keywords: quantum physics; teaching concept

From light polarization to quantum physics: Supporting lower secondary school students’ transition from gestalt to functional thinking - Bitzenbauer, Philipp; Tóth, Kristóf; Michelini, Marisa (Eurasia Journal of Mathematics, Science and Technology Education, 2024)
In this paper, we present a new minimal mathematical conceptual approach to quantum mechanics using light polarization for lower secondary school students with the aim of bringing students closer to the so-called quantum mechanical way of thinking. We investigated how students think about some of the basic concepts and fundamental laws and we found that certain concepts are quite well-understandable in younger grades too. We studied the introduction of the so-called state circle, which can faithfully represent quantum mechanical formalism without involving students in abstract algebraic calculations. We then categorized and analyzed students’ thoughts on the superposition principle and the lack of trajectory, finding that the concept of measurement and the lack of trajectory were problematic. We explored that younger students tend to hold gestalt-like mental models of quantum concepts, while at the same time being able to use visualizations correctly for reasoning in the quantum realm. Overall, this paper provides evidence in favor of introducing basic features of quantum mechanics as early as in lower secondary school.

From simulation to experiment: Using KiCad to design electric circuits in the physics classroom - Bitzenbauer, Philipp; Dandl, Kosmas; Tóth, Kristóf (Eurasia Journal of Mathematics, Science and Technology Education, 2024)
Secondary school students encounter a wide range of electronic devices in their everyday lives that are not usually covered in physics classes. Examples include mobile phone power adapters that convert high-voltage alternating current to low-voltage direct current. However, such examples are often not used sufficiently in the classroom to provide students with insights into (a) the specific applications of the electronic components used and (b) the underlying electronic design process. To fill this gap, we have designed a new context-based, easy-to-implement teaching-learning sequence that guides students to how to use the electronic design and simulation program KiCad which is being widely used by professionals in the field, (2) build their own analog experimental setup of a mobile phone power supply, and thus (3) understand how a mobile phone power supply works. The presented part of the teaching-learning sequence focuses on the use of KiCad and is designed to allow students to work individually and in groups to learn according to the think-pair-share principle based on a set of tasks we created. This paper examines the pedagogical potential of KiCad and provides a detailed description of the teaching-learning sequence and reports on initial classroom experiences: A total of N = 28 students aged 16 to 17 years participated in the unit as part of an extracurricular course and completed a questionnaire based on the Technology Acceptance Model to investigate the perceived ease of use and usability of the KiCad software. We found that despite the fact that the students had not used KiCad before, they were quite positive about the educational material as a whole and the KiCad software in particular.

From the Big Bang to Life beyond Earth: German Preservice Physics Teachers’ Conceptions of Astronomy and the Nature of Science - Bitzenbauer, Philipp; Hennig, Fabian; Lipps, Maximilian; Ubben, Malte (Education Sciences, 2023)
This article reports the findings of a qualitative study that aimed to explore the ideas of 22 preservice physics teachers regarding astronomy concepts both within and beyond the solar system, as well as their understanding of the Nature of Science in the context of astronomy. The study employed a combination of open-ended vignette tasks and ranking tasks, which were adapted from previous research. The results reveal that while the majority of the preservice teachers held appropriate conceptions of astronomy concepts, some of their ideas lacked depth and were superficial. Moreover, their understanding of the Nature of Science in the context of astronomy was found to be limited. This study highlights the importance of providing further education and training in this area, as well as the need to develop and test effective teaching strategies to enhance preservice teachers’ and physics education students’ understanding of astronomy concepts and the Nature of Science.<br

Future quantum workforce: Competences, requirements, and forecasts - Bitzenbauer, Philipp; Greinert, Franziska; Müller, Rainer; Ubben, Malte; Weber, Kim-Alessandro (Physical Review Physics Education Research, 2023)
With the increasing industrial relevance of new quantum technologies, a well-educated quantum workforce becomes increasingly crucial. The foreseeable lack of workforce raises important questions. What are the expectations regarding the future relevance of second-generation quantum technologies? What are the requirements for the workforce in the coming quantum industry? Which competences, knowledge, and skills should future employees have? In this paper, we report the results of our study that were aimed at mapping requirements and forecasts for the future quantum workforce. Our study consisted of three consecutive survey rounds. In total, we gathered 188 responses from industry and academic experts across Europe. Our study results served as an input for the development of the European Competence Framework for Quantum Technologies, delivered by the project QTEdu CSA for the European Quantum Flagship. In addition, we will discuss predictions from experts related to the future quantum workforce, including the expected industrial relevance of the main areas of quantum technologies, the need for educational efforts, and the expected influence of quantum technologies on everyday life.<br

(How) Do Pre-service Teachers Use YouTube Features in the Selection of Instructional Videos for Physics Teaching? - Bitzenbauer, Philipp; Teußner, Tom; Veith, Joaquin M.; Kulgemeyer, Christoph (Research in Science Education, 2023)
This mixed-methods study examines how pre-service teachers select instructional videos on YouTube for physics teaching. The study focuses on the role of surface features that YouTube provides (e.g., likes, views, thumbnails) and the comments underneath the videos in the decision-making process using videos on quantum physics topics as an example. The study consists of two phases: In phase 1, N = 24 (pre-service) physics teachers were randomly assigned to one of three groups, each covering a different quantum topic (entanglement, quantum tunneling, or quantum computing, respectively). From eight options provided, they selected a suitable video for teaching while their eye movements were tracked using a stationary eye tracker in a laboratory setting, and think-aloud data was collected. In the subsequent phase 2, participants were allowed to freely choose one YouTube video on a second topic of the above-mentioned ones while thinking aloud. The results reveal a significant emphasis on video thumbnails during selection, with over one-third of the fixation time directed towards them. Think-aloud data confirms the importance of thumbnails in decision-making, e.g., as evidenced by a categorization of the study participants’ arguments and thoughts voiced. A detailed analysis identifies that participants did not rely on (content-related) comments despite they have been found to be significantly correlated with the videos’ explaining quality. Instead, decisions were influenced by surface features and pragmatic factors such as channel familiarity. Retrospective reflections through a questionnaire including rating scale items support these observations. Building on the existing empirical evidence, a decision tree is proposed to help teachers identify high-quality videos considering duration, likes, comments, and interactions. The decision tree can serve as a hypothesis for future research and needs to be evaluated in terms of how it can help systematize the process of selecting high-quality YouTube videos for science teachin
CRIS-Team Scopus Importer:2023-12-29
Keywords: Instructional videos; Mixed-methods; Physics education; Quantum physics; YouTube

How do pre-service teachers view Galois theory? A questionnaire study - Bitzenbauer, Philipp; Veith, Joaquin Marc; Girnat, Boris; Winkler, Bianca; Becker, Eleonore; Becher, Richard (Eurasia Journal of Mathematics, Science and Technology Education, 2024)
Abstract algebra is an important part of mathematics teacher education as it provides the rigorous mathematical foundations for many mathematics topics covered in school classrooms. Throughout their academic career, many secondary mathematics teachers even enroll in more advanced algebra courses, which often culminate in Galois theory. However, very little is known about educational aspects of Galois theory and respective mathematics education research is scarce. We contribute to closing this gap by reporting on the results of an exploratory questionnaire study with a sample of n=39 pre-service mathematics teachers, inquiring about the raison d’être of incorporating Galois theory into teacher education: Is Galois theory viewed as useful for their later profession and which connections are drawn to the secondary mathematics classroom? On the one hand, the results of our study indicate that a vast majority of pre-service teachers do not perceive studying Galois theory as meaningful and struggle to exemplify connections between Galois theory and secondary school mathematics. On the other hand, a small share of the participants experienced Galois theory as an important part of mathematics that elegantly connects a variety of algebraic and geometric notions.

Improving Early Optics Instruction Using a Phenomenological Approach: A Field Study - Bitzenbauer, Philipp; Fliegauf, Kai; Sebald, Janika; Veith, Joaquin M.; Spiecker, Henrike (Optics, 2022)
Previous research has shown that phenomenological approaches in early optics education might be superior to traditional model-based instruction based on the light ray realm with regards to fostering students’ conceptual understanding of basic optics topics. However, it remains open to date which learning difficulties students encounter when being introduced to optics following a phenomenological approach—in particular, in comparison to the learning difficulties that are widespread among students introduced to optics via traditional model-based instruction. With this article, we contribute to closing this gap: We report the results of a quasi-experimental field study with N=189" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=189 secondary school students. We used ten items adapted from the literature in a pre-posttest design for an in-depth exploration of the conceptions of introductory optics topics acquired by N=89" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=89 students introduced to optics following a phenomenological teaching-learning sequence and compare these students’ conceptions to the ones acquired by N=100" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; color: rgb(34, 34, 34); font-family: Arial, Arial, Helvetica, sans-serif; position: relative;">N=100 peers who participated in traditional model-based instruction covering the same content topics. The results of this study substantiate earlier findings according to which phenomenological teaching might be a fruitful endeavour for early optics education, in particular, when it comes to teaching and learning about image formation by converging lenses.

Inhaltsvalidität eines Testinstruments zur Erfassung deklarativen Wissens zur Quantenoptik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
In der empirischen Unterrichtsforschung wird im Kontext von Testentwicklung oft von der Validierung eines Testinstruments gesprochen. Die Debatte über das Testgütekriterium Validität führte zu einer Verschiebung der Auffassung von Validität. Heute ist weniger von der Validität als Eigenschaft eines Tests die Rede. Vielmehr steht eine valide Testwertinterpretation im Zentrum der Sicherung von Testqualität. Dass ein Testverfahren valide Testwertinterpretation erlaubt, muss argumentativ abgeleitet werden. Die erforderlichen Argumentationsstränge sind dabei nicht standardisierbar. Insbesondere für Forschungsbereiche, in denen es nur wenig belastbare theoretische Vorarbeiten gibt, birgt das Hürden. Hier setzt dieser Artikel an: anhand eines „best-practice“-Beispiels aus der Didaktik der Quantenphysik wird aufgezeigt, wie ein solcher argumentativer Prozess methodisch erfolgen kann. Zunächst wird der Bedarf einer Neuentwicklung eines Testinstruments für die summative Evaluation eines Unterrichtskonzepts zur Quantenoptik begründet. Die Testentwicklung wird beschrieben. Inwiefern eine valide Testwertinterpretation möglich ist, wird argumentativ abgeleitet: Die Ergebnisse von einer Studie zum Lauten Denkens, sowie einer Expertenbefragung werden mit Ergebnissen einer quantitativen Pilotstudie kombiniert.

Lernende erläutern Wesenszüge der Quantenphysik: Doppelspalt und Interferometer im Fokus - Bitzenbauer, Philipp (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2021, 2022)

Mathematical sense making of quantum phenomena using Dirac notation: its effect on secondary school students functional thinking about photons - Bitzenbauer, Philipp; Hennig, Fabian; Tóth, Kristóf; Joaquin M., Veith (EPJ Quantum Technology, 2024)
Previous research has consistently demonstrated that students often possess an inadequate understanding of fundamental quantum optics concepts, even after formal instruction. Findings from physics education research suggest that introducing a mathematical formalism to describe quantum optical phenomena may enhance students’ conceptual understanding of quantum optics. This paper investigates whether using formal descriptions of quantum optics phenomena – such as photon anticorrelation at a beamsplitter or single-photon interference in a Michelson interferometer – expressed in Dirac notation, can support secondary school students in developing functional thinking about photons. To investigate this, we conducted a clusterrandomized field study, comparing the improvement in functional thinking between 67 students in the intervention group, who were taught using both qualitative and quantitative reasoning, and 66 students in the control group, who were taught using only qualitative reasoning. The results indicate that mathematical formalism can indeed promote functional thinking about photons. However, the comparison between the intervention and control groups revealed that the control group exhibited a greater increase in functional thinking than the intervention group. In response to these findings, we conducted a follow-up study aimed at gaining a deeper understanding of the cognitive load associated with both approaches. Specifically, we compared the intrinsic and extraneous cognitive load of 71 students in the intervention group with those of 65 students in the control group. The data analysis revealed that the two groups had statistically significant differences in intrinsic cognitive load while the extraneous cognitive load did not difer statistically significant, indicating a higher mental effort associated to the quantitative reasonin

Mathematics education research on algebra over the last two decades: quo vadis? - Veith, Joaquin Marc; Beste, Meeri Liisa; Kindervater, Marco; Krause, Michel; Straulino, Michael; Greinert, Franziska; Bitzenbauer, Philipp (Frontiers in Education, 2023)
Algebra is a crucial component of mathematics education as it introduces learners to the mathematical world of modeling relationships and handling abstract quantities. The increasing volume of scholarly work in the field has been analyzed qualitatively in numerous systematic reviews—a quantitative breakdown of the field, however, remains a desideratum to date. With this study we contribute to closing this gap by reporting on the results of a bibliometric analysis. We retrieved data from Scopus and Web of Science databases and analyzed 1,825 articles published between 2003 and 2022. On the one hand, we provide insight into the current state of algebra education from primary up to tertiary education by describing the scientific production and its bibliographic topography. On the other hand, we analyzed the data to identify trends and future directions. The results of our study indicate, among other aspects, that APOS Theory and Realistic Mathematics Education are emerging themes in the field that have great potential to shape future research.
CRIS-Team Scopus Importer:2023-11-10
Keywords: algebra; APOS; bibliometric analysis; mathematics education; Realistic Mathematics Education

Nanoscience and -technology in secondary education: A systematic literature review - Bitzenbauer, Philipp; Schmid, Judith Maria; Joaquin M., Veith; Truong, My Hanh; Straulino, Michael; Winkler, Bianca; Hennig, Fabian (Eurasia Journal of Mathematics, Science and Technology Education, 2023)
This article provides a review of empirical research into nanoscience and -technology (NST) education at the secondary school level with regards to (a) teaching strategies or laboratory experiments implemented and evaluated for their impact on student learning about nanotechnology aspects, (b) concept inventories and methods used to assess students’ conceptual understanding, as well as (c) students’ conceptions and learning difficulties. A database search was used to identify corresponding studies published over the last decade (2012-2021) of which eleven were included in the synthesis for further analyses after screening for eligibility. The analysis revealed that learning difficulties regarding NST topics such as the differentiation between size and scale, the surface area to volume ratio or size dependent properties are widely prevalent among learners according to the current state of the literature. While our analysis identified emerging perspectives for future research with regards to the development of psychometrically characterized concept inventories in particular and empirical investigations into students’ learning progressions on nanoscience concepts in more general, a huge effort has already been put into the development of teaching concepts or laboratory experiments suitable for secondary school classrooms.

Online Course on Quantum Physics: Reading Primary Sources with Secondary School Students - Bitzenbauer, Philipp; Zenger, Tim (Journal of Physics Teacher Education Online, 2022)
Quantum physics is the basis for many technologies that are a fundamental part of our daily lives (e.g., lasers) or that may become so in the future (e.g., quantum cryptography and quantum computing). Because of this, quantum physics is now a central aspect of many countries’ secondary school curricula. In this article, we present the design and structure of an online secondary school course for synchronous learning on the historical development of quantum physics and its modern applications. With this online course entitled “Reading Club Quantum Physics: From the Beginnings to Modern Quantum Technologies,” we want to provide teachers with an individually usable resource for reading parts of quantum physics pioneers’ original publications together with their students. For this purpose, we have didactically prepared selected articles with publication dates from 1901 to 2019 and enriched them in this course (consisting of a total of seven chapters) with various work materials. Interested teachers can access our course, without charge, for their own and their students’ use by sending an email to the corresponding author.

Phenomenological optics with self-made liquid lenses in the physics classroom - Spiecker, Henrike; Bitzenbauer, Philipp (Physics Education, 2022)
Why does a raindrop on a window pane show an image of the environment that is turned upside-down? And why does vision go blurry underwater, but is perfectly clear with diving goggles? Our everyday life is rich in optical phenomena. Unfortunately, these phenomena often play a subordinate role in Optics teaching, compared to ray constructions or mechanistic light models. In our new teaching-learning sequence designed for introductory physics courses at secondary schools, the observation of the phenomena assumes a more prominent position and the observer’s sense of sight becomes the starting point of learning about Optics. The centrepiece of our concept is the use of students’ self-made Optics inventory including liquid lenses in various experiments.<br
Keywords: optics; phenomena; experiment; self-made; teaching-learning sequence

Practitioners' views on new teaching material for introducing quantum optics in secondary schools - Bitzenbauer, Philipp (Physics Education, 2021)
In an earlier contribution in Physics Education (Bitzenbauer and Meyn 2020 Phys. Educ. 55 055031), we presented a new teaching sequence on quantum optics on the secondary school level, and we reported on promising results of a first pilot study concerning its learning effectiveness. In the sense of design-based research, the developed teaching material is now being revised in several iteration steps and optimised through feedback from teachers from the field in order to favour the implementation of the new teaching approach to quantum physics in secondary schools. We present the design principles from the literature that our teaching material’s development is based on and report on a survey of physics teachers’ practical experiences with our teaching material.<br
Keywords: quantum physics; teaching material; secondary schools; teacher survey

Quantenoptik an Schulen. Studie im Mixed-Methods Design zur Evaluation des Erlanger Unterrichtskonzepts zur Quantenoptik - Bitzenbauer, Philipp (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
With this thesis we report on a new teaching concept on modern quantum physics in secondary schools. The Erlanger teaching concept on quantum optics is presented as a teaching proposal, which tries to meet the requirements of science, didactics and teaching practice in equal measure in order to help students to acquire adequate knowledge about modern quantum physics up to quantum technologies. The Erlanger teaching concept was tested in secondary schools and the results of this evaluation are the core of this thesis: ﬁrst, a formative evaluation by means of an acceptance survey served to revise the concept based on feedback from individual learners. Then a summative evaluation in a mixed-method design was conducted. For this purpose, a newly developed test instrument for quantum optics was used in a pre-post-follow-up test design, as well as an imagination questionnaire which was adapted from literature. In addition, interviews were conducted with study participants. The main study involved N = 171 students from twelve high school courses. None of the students had any prior knowledge in quantum physics before the intervention of this stuy. N = 118 of the students completed the imagination questionnaire after the intervention. A random sample of N = 25 students also participated in the interview study. The results draw the following picture: Students seem to have an interest in modern quantum physics as it is taught in the Erlanger concept. Not only signiﬁcant increases in declarative knowledge can be observed, also the investigations of the students’ conceptions show: Although widespread student conceptions on quantum physics, such as those inﬂuenced by mechanistic ways of thinking, can also be observed here, a large subset of the students showed no mechanistically inﬂuenced ideas. The consistent avoidance of mechanistic ways of speaking and the exclusion of waveparticle dualism from quantum physics lessons, as proposed in the Erlanger teaching concept, thus have the potential that learners develop largely quantum physics-based conceptions at a very early age and are thus able to name the striking diﬀerences between classical physics and quantum physics. Quantum physics lessons that take students all the way to quantum technologies are thus basically possible in secondary schools. <br
Keywords: Physikunterricht; Quantenphysik; Photon; empirische Forschung

Quantenphysik g²reifbar unterrichten - Bitzenbauer, Philipp; Meyn, Jan-Peter (PLUS LUCIS, 2019)

Quantenphysik = Quantenphysik? Assoziationen Forschender zur Quantenphysik - Winkler, Bianca; Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2020, 2021)

Quantum Awareness im Ingenieurwesen: Welche Kompetenzen werden in der Industrie von morgen gebraucht? - Gerke, Franziska; Müller, Rainer; Bitzenbauer, Philipp; Ubben, Malte; Weber, Kim Alessandro (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
Quantentechnologien gewinnen rasant an Bedeutung und „Quantum Awareness“ wird auch im Ingenieurwesen immer wichtiger. Damit ergeben sich in der universitären Lehre neue Herausforderungen zur Ausbildung von „Quantum Engineers“. Hier setzt das Projekt an: Es werden Kenntnisse und Kompetenzen im Bereich der Quanteninformationstechnologien identifiziert, die teilweise schon jetzt, vor allem aber in Zukunft, in der Wirtschaft benötigt werden. Diese werden strukturiert, um schließlich messbare Kompetenzstufen abzuleiten.Mit einer Delphi-Studie soll eine Prognose des Bedarfs von und den Anforderungen an „Quantum Engineers“ ermittelt werden. Die Ergebnisse bilden dann die Basis zur Entwicklung eines Kompetenzmodells oder Rahmenkonzeptes. Der Vortrag thematisiert das methodische Vorgehen und den aktuellen Stand der Studie.
Keywords: Quantum Awareness; Ingenieurwesen; Anforderungen; Prognose; Delphi

Quantum Physics Education Research over the Last Two Decades: A Bibliometric Analysis - Bitzenbauer, Philipp (Education Sciences, 2021)
Quantum physics is an essential field of science education research, which reflects the high relevance of research on quantum physics and its technologies all around the globe. In this paper, we report on a bibliometric analysis of the science education research community’s scientific output in the area of quantum physics in the period from 2000 to 2021. A total of 1520 articles published in peer-reviewed physics and science education journals were retrieved from Web of Science and Scopus databases to conduct bibliometric analysis. This study aims to provide an overview of quantum physics education research in terms of scientific production, preferred publication venues, most involved researchers and countries (including collaborations), and research topics. The main findings point to a continuous increase in research output in the field of quantum physics education over the last two decades. Furthermore, they indicate a shift regarding the research foci. While formerly mainly papers on the teaching of quantum physics content were published, recently, an increase in the relevancy of empirical studies on the teaching and learning of quantum physics can be observed.<br
Keywords: quantum physics; bibliometric analysis; science education

Quantum physics ≠ quantum physics. A survey of researchers' associations - Winkler, Bianca; Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2021)
No consensus has been reached so far concerning the key topics on quantum physics suitable for secondary school teaching, despite comprehensive research. We identified the the variety of associations with quantum physics among professionals as a potential cause. From an explorative mind map study with N = 29 physics researchers, we derive six subject-specific focal points in the associations that researchers have with quantum physics.<br

Quantum science in a nutshell: fostering students' functional understanding of models - Bitzenbauer, Philipp; Ubben, Malte; Joaquin M., Veith; Merzel, Avraham (Frontiers in Education, 2023)
Fostering students' understanding of models is a challenge. However, in particular for learning quantum physics an elaborate understanding of models is required. We investigated activities to foster students' functional thinking about (quantum) models in a synchronous online course. The results of an evaluation study (N = 59) showed that the participants improved in their quantum physical thinking about photons and had slightly improved their understanding of physics models in general. A correlation analysis indicates that there are no significant correlations between the students' general understanding of models in physics and their functional understanding of quantum models. Implications of our findings for both teaching and future research with regard to quantum physics education are discussed.<br

Requirements for future quantum workforce – a Delphi study - Gerke, Franziska; Müller, Rainer; Bitzenbauer, Philipp; Ubben, Malte; Weber, Kim Alessandro (Journal of Physics: Conference Series, 2022)
With new quantum technologies and new applications comes a new need for specialists, the new quantum workforce. This brings new challenges for education that the typical quantum mechanics courses for physicists do not address. Requirements for the future quantum workforce need to be collected and training programmes created. In between, there should be a European competence framework on which to build the training programmes. One goal of the European Flagship project QTEdu is to develop this framework for second-generation quantum technologies. The Delphi study presented here serves as a basis for this: The aim is to identify knowledge and competences in the field of quantum information technologies, which are partly already needed in industry today, but especially in the future.<br

Requirements for future Quantum Workforce-Delphi-Studie: Ergebnisse der Pilotrunde - Gerke, Franziska; Müller, Rainer; Bitzenbauer, Philipp; Ubben, Malte; Weber, Kim Alessandro (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2020, 2021)

Schritt für Schritt zum Staatsexamen Mathematik Theorie und Praxis zur ersten Staatsprüfung Grund-, Mittel- und Realschullehramt - Veith, Joaquin M.; Bitzenbauer, Philipp (Springer Spektrum, 2021)
Keywords: nicht-vertieftes Staatsexamen Mathematik; Vorbereitung auf das Staatsexamen; erste Staatsprüfung Grund-; Mittel- und Realschullehramt; Prüfungstrainer Staatsexamen; Lehramt Primar- und Sekundarstufe; Staatsexamen nicht-vertieftes Lehramt Mathematik; Grund-; Mittel-; Realschule; Lehramt Mathematik; Staatsexamen Mathematik Bayern

Spooky action at a distance? A two-phase study into learners’ views of quantum entanglement - Brang, Michael; Franke, Helena; Greinert, Franziska; Ubben, Malte S.; Hennig, Fabian; Bitzenbauer, Philipp (EPJ Quantum Technology, 2024)
Quantum entanglement is a challenging concept within the field of physics education, often eluding a full grasp by both educators and learners alike. In this paper, we report findings from a two-phase empirical study into the views of entanglement held by pre-service physics teachers and physics students from various universities. In the first phase, we utilized a questionnaire consisting of open-ended questions which was completed by 31 pre-service physics teachers. The study participants’ ideas were explored using qualitative content analysis which led to the creation of rating scale items used in study phase 2. These items were administered to a broader cohort including 73 physics university students in order to capture the learners’ agreement or disagreement with the questionnaire statements, and hence, helped to validate and substantiate the in-depth insights from study phase 1. Key findings revealed widespread accurate notions, like the need to consider the entire system when examining entangled states. However, less elaborated views were also identified, including ideas such as that measurements of entangled states always show perfect (anti-)correlation. Another striking observation was the confusion between quantum entanglement and superposition. In the case of quantum teleportation, many participants seemed to have a basic grasp of the concept, although a number of misconceptions were apparent, notably the idea that quantum entanglement enables faster-than-light communication. Practically, the findings can assist educators in anticipating and addressing widespread (mis-)conceptions, paving the way for more effective instruction in quantum mechanics and its real-world applications, such as quantum cryptography and computing.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Empirical study; Entanglement; Quantum physics; Teleportation

Teacher identity in science education – Results of an empirical study on first- and third-person narratives - Veith, Joaquin M.; Bitzenbauer, Philipp (Journal of Physics: Conference Series, 2022)
We discuss the term teacher identity and its significance for teacher education and teachers' professional development. From the literature, we derive a definition of the term that associates teacher identity with first- and third-person narratives. In this way, the construct teacher identity becomes operationalizable in empirical studies: Therefore, we conducted a first exploratory study with N = 89 science and non-science teachers at five German secondary schools. This study's results indicate that the approach of identifying the construct teacher identity with first- and third-person narratives could be fruitful for future empirical research in this field.<br

Teacher identity von MINT-Lehrkräften: Explorative Studie zur Selbst- und Fremdwahrnehmung - Bitzenbauer, Philipp; Joaquin M., Veith (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung - virtuell 2021, 2021)
Die Unterrichtspraxis in allen Fächern wird maßgeblich durch das Selbstverständnis und die Persönlichkeit von Lehrkräften bestimmt. Mit dem Begriff teacher identity ist der Versuch verbunden, diese beiden Aspekte zusammenzuführen, allerdings existiert eine anhaltende Debatte über eine praxistaugliche Definition dieses Begriffs. Wir greifen diese Problematik auf und leiten aus der Literatur eine mögliche Operationalisierung des Konstrukts ab und zwar durch Unterscheidung verschiedener Narrative, die die Selbst- und Fremdwahrnehmung von Lehrkräften betreffen. Die Ergebnisse einer ersten explorativen Studie mit N = 89 Lehrkräften an fünf Gymnasien zur Selbst- und Fremdwahrnehmung von MINT-Lehrkräften deuten darauf hin, dass die Definition des Konstrukts teacher identity via Selbst- und Fremdwahrnehmungen, für zukünftige empirische Forschung in diesem Bereich fruchtbar sein kann.<br
Keywords: teacher identity; MINT; Fragebogenstudie

The core of secondary level quantum education: a multi-stakeholder perspective - Bitzenbauer, Philipp; Merzel, Avraham; Krijtenburg-Lewerissa, Kim; Stadermann, Kirsten; Andreotti, Erica; Anttila, Daria; Bondani, Maria; Chiofalo, Maria Luisa; Faletič, Sergej; Frans, Renaat; Goorney, Simon; Greinert, Franziska; et al. (EPJ Quantum Technology, 2024)
Quantum physics (QP) education at the secondary school level is still in its infancy. Not only is there ongoing discussion about how to teach this subject, but there is also a lack of coherence in the selection of concepts to be taught, both across countries and over time. To contribute to this discussion, we investigated the perspectives of N=39" role="presentation"> high school teachers, university-level physics educators, and physics education researchers regarding the essential concepts in QP and the corresponding illustrations that should be introduced at the secondary school level. We examined the prominence of different key concepts and illustrations, as well as the level of consensus among the various professional groups. Our analysis revealed that certain key concepts are universally valued across all professional groups, while others are specific to particular groups. Additionally, we explored the relationships between these key concepts and their corresponding illustrations. Overall, our study offers valuable insights into the perspectives of different stakeholders, emphasizing the essential concepts and visualizations that should be considered when designing and implementing the teaching of QP at the secondary school leve

The role of affective learner characteristics for learning about abstract algebra: A multiple linear regression analysis - Veith, Joaquin M.; Girnat, Boris; Bitzenbauer, Philipp (Eurasia Journal of Mathematics, Science and Technology Education, 2022)
Recent research has boosted the inclusion of introductory group theory into secondary and undergraduate mathematics education due to manifold potentials, e.g., with regards to the promotion of students’ abstract thinking. However, in addition to research on cognitive processes, learners’ affective characteristics have largely remained unexplored in the context of teaching and learning group theory to date. In this paper, we contribute to closing this gap: We report on an empirical study investigating n=143 students’ affective characteristics within a two-weeks course program - the Hildesheim teaching concept. In our study, this concept was used to introduce pre-service primary teachers into group theory. A multiple linear regression analysis reveals that neither mathematics-specific ability self-concept nor subject interest are significant predictors of the achieved conceptual understanding of group theory after the intervention indicating that group theory is not reserved for only the mathematically interested students or students with a high mathematics-specific self-concep
Keywords: mathematics-specific self-concept; subject interest; situational interest; group theory

The World through My Eyes: Fostering Students’ Understanding of Basic Optics Concepts Related to Vision and Image Formation - Sebald, Janika; Fliegauf, Kai; Veith, Joaquin M.; Spiecker, Henrike; Bitzenbauer, Philipp (Physics, 2022)
Prior research has shown that many secondary school students have a insufficient conceptual understanding of basic optics concepts even after formal instruction. In this paper, we empirically investigate whether a phenomenological approach might be a sensible alternative to traditional model-based instruction of introductory optics in early physics education. We report the results of a quasi-experimental field study to examine the effect of a phenomenological approach following the Erlangen teaching–learning sequence of introductory optics on N=42" role="presentation">N=42 eight graders’ acquisition of conceptual understanding related to (1) the process of vision, (2) refraction, and (3) image formation by converging lenses. We contrast the learning outcomes with those of N=55" role="presentation">N=55 control group students who participated in traditional model-based instruction. The results of this study indicate that the phenomenological approach is superior to traditional (model-based) instruction in promoting students’ conceptual understanding of basic optics concepts, in particular with regard to circumventing widespread learning difficulties related to image formation. Our results are further substantiated by a comparison of students’ situational interest in optics between both groups. This adds further arguments in favor of the use of phenomenological approaches when it comes to teaching basic optics concepts in classroom practice.
Keywords: optics; vision; image formation; secondary school; phenomenology

Towards Describing Student Learning of Abstract Algebra: Insights into Learners’ Cognitive Processes from an Acceptance Survey - Veith, Joaquin M.; Bitzenbauer, Philipp; Girnat, Boris (Mathematics, 2022)
In an earlier contribution to Mathematics, we presented a new teaching concept for abstract algebra in secondary school mathematics, and we discussed findings from mathematics education research indicating that our concept could be used as a promising resource to foster students’ algebraic thinking. In accordance with the Design-Based Research framework, the developed teaching concept is now being revised in several iteration steps and optimised towards student learning. This article reports on the results of the formative assessment of our new teaching concept in the laboratory setting with N=9" role="presentation" style="max-height: none; display: inline; line-height: normal; font-size: 13.2px; text-align: left; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; position: relative;">N=9 individual learners leveraging a research method from science education: The acceptance survey. The results of our study indicate that the instructional elements within our new teaching concept were well accepted by the students, but potential learning difficulties were also revealed. On the one hand, we discuss how the insights gained in learners’ cognitive processes when learning about abstract algebra with our new teaching concept can help to refine our teaching–learning sequence in the sense of Design-Based Research. On the other hand, our results may serve as a fruitful starting point for more in-depth theoretical characterization of secondary school students’ learning progression in abstract algebra.<br
Keywords: algebra; groups; secondary school; mathematics education

Toward Types of Students’ Conceptions About Photons: Results of an Interview Study - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Teacher Education, 2022)
We report an exploratory interview study into students’ conceptions of photons developed by learners introduced to a QED model of photons as part of an introductory course in quantum physics at the secondary school level. By combining qualitative and quantitative research methods, we extract types of students’ imaginations about photons. Furthermore, we show that teaching a QED model of the photon might help to circumvent known (naive) particle notions of the photo

Two Challenging Concepts in Mathematics Education: Subject-Specific Thoughts on the Complex Unit and Angles - Joaquin M., Veith; Bitzenbauer, Philipp (European Journal of Science and Mathematics Education, 2021)
In this paper, we focus on two particularly problematic concepts in teaching mathematics: the complex unit i and angles. These concepts are naturally linked via De Moivre’s theorem but are independently misused in numerous contexts. We present definitions, notations, and ways of speaking about these terms from mathematics education that are not valid from a subject-specific point of view. We justify how these incorrectly used definitions, notations, and ways of speaking convey a false picture of the mathematical content and present options for introducing these concepts in classroom practice in a correct way.<br
Keywords: mathematics education; complex numbers; angles; misconceptions

Two Cognitive Dimensions of Students’ Mental Models in Science: Fidelity of Gestalt and Functional Fidelity - Ubben, Malte; Bitzenbauer, Philipp (Education Sciences, 2022)
A poorly elaborated learner’s understanding of models has been reported to be one of the major sources for learning difficulties in the quantum domain. To be able to provide physics education in schools with evidence as to how this problem can be tackled, a deeper theoretical understanding of the structure of learners’ mental models in quantum physics seems essential. In this respect, previous research has proposed two dimensions in learners’ mental models in the atomic hull context, labelled Fidelity of Gestalt and Functional Fidelity. In this article, we investigate whether this proposed two-factorial structure can be transferred to quantum concepts beyond the atomic hull context. To approach this, we surveyed the structure of students’ mental models in the context of photons’ properties and behavior. We conducted a questionnaire study: 170 secondary school students completed a survey instrument adapted from the literature. Using exploratory factor analysis, the two factors Fidelity of Gestalt and Functional Fidelity to describe the students’ mental models could be replicated for the photon context. We provide a selection of results from physics education literature to reveal that our two-factor framework to describe the students’ mental models seems to be a promising endeavor in the landscape of science education research in general.<br
Keywords: mental models; empirical investigation; quantum physics; cognitive structure

Unterrichtskonzept zur Optik mit self-made Flüssigkeitslinsen - Spiecker, Henrike; Bitzenbauer, Philipp (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2021, 2022)

Von Koinzidenzen zu Wesenszügen der Quantenphysik: Erste Ergebnisse einer summativen Evaluation des Erlanger Unterrichtskonzepts zur Quantenoptik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
Mit dem Erlanger Unterrichtskonzept zur Quantenoptik wird das Ziel verfolgt, eine moderne Sichtweise auf die Quantenphysik zu vermitteln. Lernende sollen anschlussfähiges Wissen bis hin zu den Wesenszügen der Quantenphysik aufbauen. Im Rahmen einer summativen Evaluation mit Schülerinnen und Schülern der gymnasialen Oberstufe wird das Konzept evaluiert. Ein mixed-methods-Ansatz wurde gewählt, um verschiedene Perspektiven auf die Lernprozesse nachzeichnen zu können. Erste Ergebnisse aus einem Fragebogen zum deklarativen Wissen in Quantenoptik im Prä-Post-Follow-Up-Testdesign sowie einem Vorstellungsfragebogen zur Quantenphysik werden vorgestellt. Es zeigt sich: Lernende gelangen zu einem angemessenen Begriffsverständnis zur Quantenoptik und bauen ein überwiegend adäquates Verständnis der Wesenszüge auf, aber eine Teilchenvorstellung von Photonen scheint stabil zu sein.

Von Schnee- und Elektronenlawinen: Entwicklung eines Erklärvideos zu Einzelphotonendetektoren - Donhauser, Anna; Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
Analogiebildung ist ein methodisches Werkzeug zur Förderung naturwissenschaftlicher Lernprozesse. Für das Erlanger Unterrichtskonzept zur Quantenoptik wurde zur Vermittlung des Lernbereichs Einzelphotonendetektoren eine Analogie erarbeitet. Die Funktionsweise der Einzelphotonendetektoren wird dabei mit dem Entstehen und Abgehen von Schneelawinen verglichen. Mittels eines für die Vermittlung dieser Analogie konzipierten Erklärvideos werden die Schülerinnen und Schüler im Rahmen einer Unterrichtssequenz schrittweise durch die funktionalen Zusammenhänge und Entsprechungen geführt. Die Akzeptanz der Analogie als Lernhilfe wurde in Akzeptanzbefragungen mit Schülerinnen und Schülern der gymnasialen Oberstufe evaluiert.
Keywords: Erklärvideo; Quantenphysik; Analogie; Didaktische Rekonstruktion

Was ist so besonders an Superpositionen? Von Überlagerungen in der klassischen Wellenlehre zu Superpositionen in der Quantenphysik - Bitzenbauer, Philipp; Heusler, Stefan; Ubben, Malte (Naturwissenschaften im Unterricht. Physik, 2023)

What Group Theory Can Do for You: From Magmas to Abstract Thinking in School Mathematics - Veith, Joaquin M.; Bitzenbauer, Philipp (Mathematics, 2022)
In this paper, we present a novel concept for an abstract algebra course at the secondary school level. Against the backdrop of findings from mathematics education research, we discuss benefits that arise from teaching abstract algebra to secondary school students. We derive suitable content items as well as educational ideas on how to implement them into mathematics classrooms. We build on frameworks from mathematics education research to design a teaching-learning sequence that enables a beneficial learning trajectory across three units— the result is a coherent teaching concept that encompasses Magmas in a hands-on way. It can be used for either extra-curricular activities or advanced courses in mathematics classes, and can be of benefit for mathematics learners.<br
Keywords: algebra; groups; magmas; secondary school; mathematics education